SOLIDARITAS SOSIAL DI DALAM ORGANISASI ANAK RANTAU PACITAN DI KOTA PEKANBARU - Wardana, Slamet; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is in the background by migrants from Pacitan Regency who are in Pekanbaru City. migrants from Pacitan district incorporated Organization Anak Rantau Pacitan in Pekanbaru City in the activities of their organization show the form of social solidarity among members of the organization, in life in the city of Pekanbaru. With the problem formulation to know the role of Organization Anak Rantau Pacitan to the members of the organization and to know the role of social solidarity created in Organization Anak Rantau Pacitan in Pekanbaru City. The theory used is the theory of social groups, and Durkheim Emile theory of social solidarity. The research uses descriptive qualitative research method so that the emerging analysis is the words arranged in expanding text. With the technique of taking research subjects based on Pourposive Sampling is the technique of selecting informants based on certain considerations. From the results of research in the field can be seen that Organization Anak Rantau Pacitan has a role as a family in the city of Pekanbaru. Organization Anak Rantau Pacitan as a social event to the home village, as a controller and adaptation in a new environment, and as a pioneer of attitude adjustment in the new environment. From the social solidarity created among the members of the organization is the nature of mechanical solidarity characterized by low division of labor, strong collective consciousness, dominant repressive relations, the importance of consensus on the normative pattern, the relative interdependence is low and rural. The result of the establishment of social solidarity among Organization Anak Rantau Pacitan members is the success of building the economic life, the success of maintaining ethnic identity, the success of creating social solidarity among fellow community originating from Pacitan Regency in Pekanbaru City Keywords: immigrants, social groups, social solidarity